The Relevance of Infant Outcome Measures: A Pilot-RCT Comparing Baby Triple P Positive Parenting Program With Care as Usual - Popp, Lukka; Fuths, Sabrina; Schneider, Silvia (Frontiers in Psychology, 2019)
Problems in infant mental health such as the ability to experience, regulate, and express emotional states is expressed in behavioral problems like excessive crying, feeding and sleeping problems. Parenting programs are popular but their effectiveness on infant mental health remains uncertain. Possibly, because recent studies have focused only on parental and parent-child measures while they miss to assess infant behavioral measures. The goal of this pilot study is to fill in this gap by assessing infantile behavioral measures. We investigated the acceptance and first indicators of efficacy of the universal group parenting training Baby Triple P (BTP) compared to a care as usual (CAU) control condition focusing on early behavioral problems. In all, 49 couples were randomly allocated to receive either eight BTP sessions before birth and per telephone after birth or to take part in CAU. Infant behavior was assessed with a diary and a structured diagnostic interview. Parental self-report measures of partnership quality and parental competence were assessed before birth, 10 weeks after birth and at 6-month follow-up. Since the parent training was conducted before the birth of the child, the child's mental health could not be assessed before the parent training. Thus, for this variable no within measurement (pre - post) could be carried out and intention-to-treat analysis was not possible. However, a between group analysis comparing BTP against CAU took place to assess effectiveness of BTP on children´s mental health. Mothers and fathers rated the program as feasible and relevant. Results indicate significant group differences in crying behavior sixth months after birth to the benefit of the intervention group. No beneficial outcomes were found for feeding and sleeping problems in infants or partnership quality, parental sense of competence in parents. Due to an unrepresentative high level of education of the participating parents and the small sample size, these findings can be considered preliminary. Nevertheless, these results allow to further investigate the effectivity of BTP in large-scale clinical trials. Behavioral diaries or diagnostic interviews for early mental health problems should be routinely implemented in RCTs in order not to miss possible behavioral changes in infants.